2012
DOI: 10.1103/physrevb.85.184428
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation transition of the magnetic proximity polarization in Fe/(Ga,Mn)As bilayers

Abstract: Recently, it has been observed that thin ferromagnetic Fe films deposited on top of (Ga,Mn)As layers induce a significant proximity polarization in the (Ga,Mn)As film even at room temperature. Furthermore, it was found that a thin interfacial region of the (Ga,Mn)As film is coupled antiferromagnetically to the Fe layer. Here we report a series of combined x-ray magnetic dichroism and superconducting quantum interference device magnetometer measurements for Fe/(Ga,Mn)As bilayers where the (Ga,Mn)As layer thickn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…reaches a maximum of 30%, which is in good agreement with reported values at room temperature [10][11][12]. The Mn XMCD asymmetry value is about 15% at 4 K, considerably larger than results reported earlier [13,23], indicating that a larger number of the Mn ions is contributing to the magnetic order in our samples than expected from the nominal concentration of Mn in the (Ga,Mn)As layer, with excellent agreement with published results [21,[26][27][28][29][30][31].…”
Section: B Polarized Neutron Reflectometrysupporting
confidence: 94%
See 3 more Smart Citations
“…reaches a maximum of 30%, which is in good agreement with reported values at room temperature [10][11][12]. The Mn XMCD asymmetry value is about 15% at 4 K, considerably larger than results reported earlier [13,23], indicating that a larger number of the Mn ions is contributing to the magnetic order in our samples than expected from the nominal concentration of Mn in the (Ga,Mn)As layer, with excellent agreement with published results [21,[26][27][28][29][30][31].…”
Section: B Polarized Neutron Reflectometrysupporting
confidence: 94%
“…This observation differs from several previous studies of Fe/(Ga,Mn)As bilayers [10][11][12], where an antiparallel alignment was observed between the Fe layer and the Mn moments in the bulk of the GaMnAs layer. However, a recent study of exchange coupling in such bilayers also revealed that the type of coupling [antiferromagnetic (AFM) or FM] depends strongly on the thickness of the (Ga,Mn)As layer [13], AFM coupling of bulk (Ga,Mn)As occurring in thick (Ga,Mn)As layers, and FM alignment becoming dominant when the (Ga,Mn)As layers become ultrathin (below about 10 nm in Ref. [13]).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 96%
See 2 more Smart Citations
“…To overcome this limitation, the use of artificial 35 heterostructures combining ferromagnetic films with ferro-or 36 piezo-electric substrates has been explored [8][9][10][11][12].…”
mentioning
confidence: 99%